The Impact of Adopting International Financial Reporting Standards on the Quality of Earnings by Applying them to the Basic Materials Sector in The Saudi Financial Market - Al-Subaie, Abdullah Mansour; Hasan, Mohammed Faisal (The Arab Journal of Administration, 2024)
The study aimed to determine the effect of the basis for preparing standards on the quality of profits, given the importance of accounting standards in achieving the quality of profit management, and because of the financial crises that occurred in the financial markets, using data from a sample of 40 companies. During the period from 2014-2019, the study used the method of correlation analysis and standard deviations to find the relationship between the independent variables and the dependent variables. The study concluded that the application of international financial reporting standards led to reducing profit management practices, and therefore adopting international accounting standards as a binding standard contributed to enhancing transparency and credibility in financial reports and making them more valuable and useful for investors and other users. The study recommended the necessity of developing precise policies and procedures for profit management and developing precise policies and procedures that limit profit management and work to ensure compliance with accounting standards, laws and regulations in force.